2012
DOI: 10.4049/jimmunol.1201993
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Suppressor CYLD Controls the Function of Murine Regulatory T Cells

Abstract: CYLD was originally identified as a tumor suppressor gene mutated in familial cylindromatosis, an autosomal dominant predisposition to multiple benign neoplasms of the skin known as cylindromas. The CYLD protein is a deubiquitinating enzyme that acts as a negative regulator of NF-κB and JNK signaling through its interaction with NEMO and TNFR-associated factor 2. We have previously described a novel mouse strain that expresses solely and excessively a naturally occurring splice variant of CYLD (CYLDex7/8). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 44 publications
3
39
0
Order By: Relevance
“…2012). CYLD-deficient mice display a markedly increased number of Tregs in the periphery, but not in the thymus.…”
Section: Ubiquitination In Various Immune Cell Signaling Cascadesmentioning
confidence: 99%
“…2012). CYLD-deficient mice display a markedly increased number of Tregs in the periphery, but not in the thymus.…”
Section: Ubiquitination In Various Immune Cell Signaling Cascadesmentioning
confidence: 99%
“…Studies using knockout mice revealed a role for CYLD in T cell biology (67)(68)(69)(70). In these studies, the absence of CYLD resulted in reduced accumulation of mature thymocytes and peripheral T lymphocytes.…”
Section: Discussionmentioning
confidence: 91%
“…In these studies, the absence of CYLD resulted in reduced accumulation of mature thymocytes and peripheral T lymphocytes. In addition, the differentiation of the CD4 ϩ T lymphocytes into T regulatory cell subsets was halted (67)(68)(69)(70). Cleavage of CYLD by the cellular paracaspase MALT1 was necessary for proper activation of CD4 ϩ T cells in response to T cell receptor stimulation (57).…”
Section: Discussionmentioning
confidence: 99%
“…CYLD also limits tTreg generation due to antagonism of NFκB signaling [142]. Mice expressing a mutant CYLD that is incapable of binding the targets TRAF2 and NEMO displayed hyperactive T cell proliferation and activation accompanying poorly restrained NFκB activity.…”
Section: The Deubiquitinases: the Other Side Of The Storymentioning
confidence: 99%
“…As with CYLD deficiency, Treg frequencies in these mice were elevated in the absence of functional CYLD [140] – an observation perhaps expected due to the importance of both TGFβ and NFκB signaling in early tTreg development [143]. However, Tregs with inactive CYLD were less effective suppressors than their wild type counterparts [142], a potential example of the distinct consequences of robust NFκB activation for Treg development and Treg function. It was recently revealed that PKCθ, a facilitator of TCR/CD28-induced NFκB signaling, binds to CYLD in T cells antagonizing the DUB’s inhibition of NFκB and NFAT transactivation.…”
Section: The Deubiquitinases: the Other Side Of The Storymentioning
confidence: 99%